Emergence and early institutionalization of competition in higher education: evidence from Finnish business schools - Kettunen Kerttu; Alajoutsijärvi Kimmo; Hunnes John Arngrim; Pinheiro Rómulo (Springer, 2025)
This paper investigates the emergence and early institutionalization of competition in higher education (HE), specifically in business schools. First, building on key contributions from economics, management studies, sociology, and HE research, we develop propositions on competition in HE and formulate our theoretical framework. Second, we apply this framework to explore competition in Finnish business schools. We argue that business schools constitute an interesting field for studying competition in HE because they are the frontrunners and champions of competition-based views in HE. Our main contribution is a novel explanation of the preconditions, emergence, and early processes of institutionalization that drive HE institutions to compete and collectively produce the observed competitive transformation.